Photobiomodulation therapy for the prevention of acute radiation dermatitis in breast cancer patients undergoing hypofractioned whole‐breast irradiation (LABRA trial). Issue 3 (4th September 2021) - Robijns, Jolien; Lodewijckx, Joy; Puts, Sofie; Vanmechelen, Sofie; Van Bever, Leen; Claes, Stefan; Pannekoeke, Luc; Timmermans, An; Noé, Leen; Govers, Mieke; Van de Werf, Evelyn; Maes, Annelies; et al.
Abstract: Objectives: To evaluate the efficacy of photobiomodulation therapy in breast cancer patients post‐lumpectomy undergoing hypofractionated whole‐breast irradiation (HF‐WBI) for the prevention and management of acute radiodermatitis (ARD). Materials and Methods: A randomized, multicentric clinical trial (LABRA trial, NCT03924011) was set up at the Limburg Oncology Center, including the Jessa Hospital (Hasselt, BE) and Ziekenhuis Oost‐Limburg (Genk, BE). A total of 71 breast cancer patients planned to undergo HF‐WBI were randomized to one of the two study arms: the control group ( n  = 32) or the PBM group ( n  = 39). The PBM group received the standard institutional skincare combined with PBM (2×/week) during the complete radiotherapy (RT) course. Patients in the control group received the standard skincare combined with placebo treatment (2x/week). Patients' skin reactions were evaluated weekly during the RT treatment by using the modified version of the Radiation Therapy Oncology Group (RTOG) criteria. Results: At week 3 of RT, one patient presented a grade 2 and one patient a grade 3 skin reaction in the control group, while in the PBM group, all patients still presented grade 1 ARD. At the final RT session 28% of the patients presenting grade 2–3 ARD, while in the PBM group 10% presented grade 2 and no grade 3 ARD. PBM reduced the incidence of severe ARD by 18%. However, the difference was not significant ( p  = 0.053). Conclusion: Based on the LABRA trial results, PBM seems not able to reduce the incidence of severe ARD in breast cancer patients undergoing HF‐WBI. Research in a larger patient population is recommended.